A sourcebook on banking law in Singapore & Malaysia - Soe, Myint U. (Singapore : Institute of Banking and Finance, 1977)
This volume is a supplementary text on banking law in Malaysia and Singapore.
Includes index.
lje 25/01/2019
Loans
Keywords: Banking law; Singapore; Malaysia